KOSMOLOGI LAUT DAN ETIKA LINGKUNGAN: ANALISIS ANTROPOLOGI EKOLOGI TERHADAP PRAKTIK KEHIDUPAN SUKU BAJO DI DESA MEKAR KECAMATAN SOROPIA KABUPATEN KONAWE - Mursin Mursin; Zulzaman Zulzaman; Hardin Hardin (Yayasan Literasi Sains Indonesia, 2025)
Ecological wisdom is an integral part of the life practices of the Bajo people, who have traditionally depended on marine ecosystems as their primary living space. This study aims to examine the forms of ecological wisdom of the Bajo, reflected in customary prohibitions, philosophical values, and local knowledge that regulate the relationship between humans and the marine environment. Customary prohibitions such as restrictions on fishing during certain periods, limits on the use of destructive fishing gear, and bans on taking marine life during breeding seasons function as social mechanisms to maintain ecosystem balance. The philosophical values of the Bajo people view the sea as a sacred living space with spiritual significance thus it must be respected and its sustainability preserved. This perspective shapes an ecological ethic that emphasizes the principle of harmony between humans and nature, as well as intergenerational responsibility. In addition, the local knowledge of the Bajo people regarding seasons, ocean currents, wind directions, and the behavior of marine organisms serves as a basis for determining fishing times and patterns of selective resource use. These practices demonstrate that the ecological wisdom of the Bajo people functions both as a system of cultural values and as an adaptive strategy for dealing with the dynamics of the marine environment. Thus, the ecological wisdom of the Bajo people plays an important role in supporting the sustainable conservation of coastal and marine environments.